PENGENALAN DAN PELATIHAN PENYUSUNAN PROPOSAL HIBAH KEGIATAN BERWIRAUSAHA MAHASISWA INDONESIA UNTUK MENINGKATKAN MINAT WIRAUSAHA MAHASISWA - Fahmi Yahya; Hermansyah Hermansyah; Syafruddin Syafruddin; Muhammad Irham; Supriadin Supriadin; Irfan Hamonangan Tarihoran (FKIP Universitas Samawa, 2021)
Indonesian Student Entrepreneurial Activities (KBMI) is one of the government programs in order to encourage the emergence of young entrepreneurs in universities. This grant is organized by the Ministry of Education and Culture (kemdikbud) through the Directorate General of Belmawa. Every student has the opportunity to participate in KBMI. However, not all students know the information about this grant. So we feel the need to introduce as well as provide training to students to prepare KBMI grant proposals. With this activity, it is hoped that students will be more motivated to become entrepreneurs and be able to make proposals as well as possible. This activity was carried out in February 2021 in the hall of the STKIP Pracendikia NW Sumbawa, attended by students and prospective supervisors. The activities run smoothly and according to plan. Participants were very enthusiastic and followed the activity until the end. Activities like this are expected to become routine activities to increase student motivation in entrepreneurship and participate in student grants.